Bentuk Pola Asuh dalam Bersahabat dan Komunikatif Remaja Lawan Jenis Suku Banjar di Desa Jamil Kalimantan Selatan - Sumiati, Sumiati (Jurnal Pendidikan Kewarganegaraan, 2024)
The form of misunderstanding in friendship/friendship and communication that occurs in the parenting patterns of families in Jamil Village, South Kalimantan towards teenagers of the opposite sex has given rise to unpleasant relationships between communities, giving rise to behavior that is considered bad by members of the community, giving rise to behavior that is not good for the community. public. Teenagers of the opposite sex from the Banjar tribe in Jamil Village immediately experienced control by village officials and the community, thereby suppressing several active and positive social movements. This researcher used qualitative methods with a phenomenological approach to help understand the life experiences of Banjar youth of the opposite sex who are friendly and communicative in social interactions from the previous perspective. For this reason, researchers make every effort to observe and listen to informants telling their experiences. Researchers must be able to accept the pure meaning of each experience and demand transcendental interpretations and new understandings. Therefore, communicative communication between teenagers in the form of friendship between teenagers of the opposite sex from the Banjar tribe in Jamil village, South Kalimantan, providing a friendly and communicative culture for teenagers of the opposite sex from the Banjar tribe, can be a solution to existing problems. However, teenagers of the opposite sex who are raised with an authoritative and authoritative upbringing do not violate society's values and norms. Creating a harmonious and tolerant family life whose authoritarian educational typology is not suitable for teenagers. Adolescents of the opposite sex from the Banjar tribe have a typology of liberal parenting. These two types of parenting are designed to regulate the forms of friendship and interaction between teenagers of the opposite sex. Society in relation to oneself and the implementation of one's duties and functions.